Pengaruh Terapi Bermain Terhadap Trauma Healing Pada Anak Korban Bencana Alam - Dhito Dwi Pramardika; Jelita Siska Herlina Hinonaung; Astri Juwita Mahihody; Grace Angel Wuaten (Universitas Faletehan, 2020)
The impact of natural disasters is loss of life, loss of property, and environmental damage. However, the psychological impact is often ignored especially in children. If not addressed, it can affect on their growth and development. This study aims to determine the effects of trauma healing on children victims of landslides and flash floods in Kampung Belengang, Sangihe Islands Regency, North Sulawesi Province. The experimental group were given play therapy while the control group were not given the intervention. The type of research is quasi-experimental with two unpaired samples. The analysis used to test the difference of the effects is by using Mann-Whitney test. The samples of this study were 16 children in the experimental group and 10 children in the control group. The results of this study show the difference in the average value of the experimental group (17.6056) and the average value of the control group (0.0000). To conclude, there is a significant difference between children who are given play therapy and the control group (p = 0.000).